2016
DOI: 10.1016/j.bbadis.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin is a proximal effector of leptin-mediated non-alcoholic steatohepatitis (NASH) fibrosis

Abstract: Introduction Liver fibrosis develops when hepatic stellate cells (HSC) are activated into collagen-producing myofibroblasts. In non-alcoholic steatohepatitis (NASH), the adipokine leptin is upregulated, and promotes liver fibrosis by directly activating HSC via the hedgehog pathway. We reported that hedgehog-regulated osteopontin (OPN) plays a key role in promoting liver fibrosis. Herein, we evaluated if OPN mediates leptin-profibrogenic effects in NASH. Methods Leptin-deficient (ob/ob) and wild-type (WT) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Multiple studies have shown that OPN is involved in hepatic fibrosis and that neutralization of OPN is effective in abrogating fibrosis [4,5, 1215]. Our previous work demonstrated that EGCG can decrease OPN expression through OPN mRNA degradation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple studies have shown that OPN is involved in hepatic fibrosis and that neutralization of OPN is effective in abrogating fibrosis [4,5, 1215]. Our previous work demonstrated that EGCG can decrease OPN expression through OPN mRNA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis develops when chronic liver injury activates progenitor cells to repair tissue, but these multipotent cells often become dysfunctional with sustained injury and induce fibrogenic repair and excess cell growth [4, 5]. The hallmark of liver fibrosis is the accumulation of extracellular matrix proteins.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations